Cost-effective surgical management of liver disease in an university hospital: A retrospective study - Tseka, Ioanna; Chrisofos, Michael; Kontis, Elissaios; Triantafyllou, Christos; Kokoropoulos, Panagiotis; Arkadopoulos, Nikolaos (Health & Research Journal, 2022)
Background: Hepatobiliary surgery is a high-end surgery comprising of complex operations associated with high economic burden to a healthcare system. The aim of this study was to evaluate the cost-effectiveness of a hepatobiliary surgery highly standardized operative protocol, that minimizes intraoperative and postoperative costs, implemented by the same surgical team, in a Greek university hospital for a five-year period (2012-2016). Method and Material: The digital medical records of all patients undergoing liver resection at a tertiary university hospital from January 2012 to December 2016 by a single surgical team were retrospectively reviewed. The financial cost of the patients’ treatment was calculated in collaboration with the hospital’s logistics department, and it involved all preoperative, intraoperative, and postoperative expenses from admission to discharge, excluding physician fees and salary cost of the hospital’s nurses. Results: In this study, 127 patients underwent hepatectomy. The patient’s health status was improved after the surgery in most of the cases (121, 95.2%). The mean Length of Stay (LOS) was 13.4 (SD±17.3) days. The mean total hospitalization cost was 4,729 (SD ± 5,486) euros (€), while the cost of surgery, the higher mean cost was noted in 2013 (925, SD±974.64 €) and the lower in 2015 (142, SD±219 €). Conclusions: This protocol allows the performance of hepatectomies with a significantly decreased cost without compromising patient outcomes.